New Sight of Intelligent Algorithm Models and Medical Devices in Bioengineering: Updates and Directions - Luca Mesin (Bioengineering)
The integration of artificial intelligence (AI) models and advanced medical devices has led to significant advancements in healthcare, rehabilitation, and biomedical research [...]